SOCIAL FACTORS IN THE FORMATION OF THE VALUE OF EDUCATION - Bekdavlat Aliyev (Modern American Journals, 2025)
This article analyzes the social factors of the process of forming educational values of Uzbek youth. It is shown that the spiritual environment in society, the family, educational institutions, the media, and the influence of modern information technologies play an important role in determining the worldview of young people. At the same time, the importance of harmonizing national and universal values, strengthening spiritual and moral education in the educational process, and introducing innovative approaches is highlighted. The formation of educational values of young people provides scientific justification for ensuring the spiritual development and sustainable development of society.
Keywords: Values, globalization, national heritage, spiritual development, youth, national idea, educational values, social factors, family, educational institution, information technologies, spiritual and moral education, national and universal values, innovative approach.